Genetic diversity of Ustilago scitaminea (Syd.) Sudan isolates evaluated by differential sugarcane varieties under field conditions - Marchelo-d’Raga, Philip; Mohamed, Yousif; Dafalla, Gasim (المجلة الزراعية; مجلد 9 عدد 2 (2011), 2011)
Field experiments were conducted at the Sugarcane Research Centre, Guneid (lat. 15 o N, long. 33 o E), in seasons 2006/07 and 2008/09. The objectives were to biologically characterize six Sudan isolates of Ustilago scitaminea (Syd.) collected from different geographic locations; and, were designated as: GN1 (Guneid, NCO 376 isolate); GN2 (Guneid, CO 527 isolate); GN3 (Guneid, CO 6806 isolate); SN (Sennar, CO 527 isolate); AB (Abbasiya, isolate from mixed varieties); and NH (New-Halfa, CO 527/ CO 997 isolate) by a set of 25 differential sugarcane varieties. All inoculations were done artificially by Taiwanese pin prick method (TPPM) and dip method (DM). Results identified four pathotypes. The first and second groups; GN1, GN2 and GN3 occur in Guneid, while the third group; SN and  NH occur in Sennar and New Halfa and the fourth group AB in Abbasiya (Kenana/ Assalaya area). All four pathotypes were highly similar in pathogenicity and have relatedness percentages of 60 to 85%. Isolates GN1, NH and AB were slightly distinct and associated with virulence and, AB with avirulence, respectively. The other isolates were difficult to separate. Therefore, the absence of an isolate of high virulence indicates that the occurrence of smut in the current resistant variety CO 6806 is largely due to variety degradation/or resistance erosion and not due to a pathogenic entity of the smut pathogen. The study recommends an expanded screening program for smut resistance evaluation to make available a large number of resistant sugarcane varieties coupled with careful selection of seed cane      أجريت هذه التجربة بمركز بحوث قصب السكر – الجنيد (خط عرض 0 15 ش، طول   0 33ق) على مدى ثلاثه مواسم متتالية 2006/07، 2007/ 08 و2008/09 بهدف التمييز بايولوجياً لعدد سته عزلات مختلفة من الفطر U. scitaminea متواجدة فى السودان جمعت من مناطق جغرافية مختلفة سميت بالجنيد 1 (GN1) – وهو عزل من منطقة الجنيد من الصنف   - NCO376 ،الجنيد 2 (GN2 ) – عزل من منطقة الجنيد من الصنف CO527 - ، الجنيد 3(GN3) – عزل من منطقة الجنيد من الصنف CO6806  -، والصنف سنار – عزل من منطقة سنار (SN) من الصنف  527CO - ، عباسية (AB) – عزل من منطقة العباسية من هجن مختلفة من قصب السكر - ، حلفا الجديدة (NH) عزل من منطقة حلفا الجديدة من الأصناف CO527،و CO997. ميزت بايولوجيا بأستخدام طقم مكون من 25 صنف محلى من قصب السكر . أحدثت عدوى صناعية بالمرض فى أصناف قصب السكر المختبرة بطريقتي إحداث الثقب و الغمر. أوضحت النتائج المختلفة أن عزلات الفطر U . scitaminea  الموجودة بالسودان متشابهة. عموما قسمت لأربعة سلالات ممرضة والتى عرفت ب :- السلالة الاولي والثانية  .GN1 GN2و GN3 فى الجنيد .السلالة الثالثة  SN و NH وجدا فى كل من حلفا الجديدة وسنار .السلالة الرابعة AB وجدت فى المنطقة الجغرافية لعسلايا وكنانة . وجدت كل العزلات الممرضة الأربعة شديدة التشابه من حيث الامراضية  وذات درجة قرابة 60-85 % ، .عموما   GN1و  NH مختلفة بدرجة طفيفة فى حين أن الاخريات من الصعب التفريق بينهما.  فالعزل GN1 ذو قدرة طفيفة فى شدة إحداث المرض  والعزل AB ضعيف القدرة فى شدة إحداث المرض جنبا للعزلGN2 , GN3 والعزل SN متوسط فى شدة إحداث المرض. عموما عدم وجود عزل فطرى شديد فى حدة الإصابة فى قصب السكر يدل على أن بعض حالات الإصابة مؤخرا فى الصنف CO6806 المعروف بشدة المقاومة لمرض التفحم السوطى يدل على تدهور فى الصنف نفسه وليس بسبب العزل المسبب للمرض . توصى الدراسة بوضع وتحديد برنامج لتقييم دورى لمستوى مقاومة الأصناف المزروعة ضد مرض التفحم السوطى لوضع رؤية واسعة لأصناف مقاومة من قصب السكر . بالإضافة إلى إستمرارية الممارسات الحقلية الجارية مع التجديد والإهتمام باختيار تقاوى قصب السكر .